Doctor-Patient Relationship as Dancing a Dance - Jose, Luis Turabian (Journal of Family Medicine, 2018)
The transcendence of the doctor-patient relationship is given by the confirmed fact of its influence on the results of health care. Several models of doctor-patient relationship can be described, but evidence of improved compliance, satisfaction and recall of physician information has been found in patient-centered consultations. Since these concepts of doctor-patient relationship and patient-centered consultation have multiple facets, they are complex to understand and teach. Using a metaphor is a tool that can be useful in these situations. We could say that the "good" doctor-patient relationship is a process where an "alliance" is created: a process in which the doctor adapts to the rhythm of the patient and little by little can help him move towards healthier scenarios; that is, detect "what dance the patient dances and like a good dancer, take a step back, another forward, dancing and pacing with the patient. But there is not a single type of "good" or "adequate" doctor-patient relationship; there is not "a single dance that the patient dances". If "the doctor has to dance with the patient", he has to know that there are many types of dance! The doctor will have to dance dances such as Cha-Cha (which has to be slow or very fast to dance), the Mambo (where the music is faster and the rhythm more complicated - the relationship with an urgent patient); the Merengue (which is danced like walking - informal doctor-patient relationship); el Pasodoble (that you have to dance with a haughty air, but not with rigidity -synchronizing assertiveness and empathy); The Salsa (where you have to learn the basic step separately - discontinuity of the doctor-patient relationship), among others.
Keywords: Physician-Patient Communication; General Practice; Framework; Physician-Patient Relations; Communication Training; Metaphor; Qualitative research